Cluster Effect of International Transport Routes. Issue 1 (4th March 2018) - Andreev, V.A.; Ostropol'tsev, S.Iu.
Abstract : An econometric forecast to 2025 of the volume of container shipments along the Primor'e-1 and Primor'e-2 transport routes reveals the preconditions for the formation of transborder transport and logistics clusters in northeast Asia. The article argues that international transport corridors are important for inclusion of the economic entities of the Primorsky Krai in the international system of intermodal and multimodal shipping services. In addition, it concludes that the implementation of comprehensive projects is important for the integration of Russian and global multimodal operators and also for the creation of transport and logistics centers in the border regions of the Primorsky Krai.